Roland Barthes Semiotic Analysis of the Interpretation of Body Shaming Issue in Tall Girl Movie - Fatimah, Nofia Ayu; Wirawanda, Yudha (Universitas Muhammadiyah Surakarta, 2023)
Film is one of the media that is widely favored by the public, with visual art displayed by the public as if they can feel the continuity of the film with the reality of real life, as well as the action of body shaming in this film. Body shaming is an act of negatively commenting on body shape that can cause mental disorders and depression to the victim. One of the movies that discusses the action of body shaming is the movie